Achilles tendon ultrasonography in the clinical screening of familial hypercholesterolaemia – a cross-sectional analysis (Swiss Medical Weekly, 2023)
BACKGROUND AND AIMS: People with familial hypercholesterolaemia are 13 times more likely to develop cardiovascular disease than the general population. However, familial hypercholesterolaemia remains largely underdiagnosed. Tendon xanthoma is a specific clinical feature of familial hypercholesterolaemia and its presence alone implies a probable diagnosis of familial hypercholesterolaemia according to the Dutch Lipid Clinic Network Score (DLCNS). The aim of the study was to determine whether ultrasound detects more Achilles tendon xanthomas (ATX) than clinical examination.METHODS: We recruited 100 consecutive patients with LDL-C ≥4 mmol/l. Achilles tendons were evaluated through clinical examination by trained physicians and sonographic examination by another physician blind to the results of clinical examination. Blind second readings of ultrasound images were performed by an expert in musculoskeletal ultrasound. We compared the proportion of patients with ATX detected by either clinical examination or ultrasound and the proportion of patients with a probable/definite familial hypercholesterolaemia diagnosis on the DLCNS before and after ultrasound.RESULTS: Mean (SD) age was 47 (12) years; mean highest LDL-C was 6.57 mmol/l (2.2). ATX were detected in 23% of patients by clinical examination and in 60% by ultrasound. In consequence, 43% had a probable/definite diagnosis of familial hypercholesterolaemia on the DLCNS using clinical examination compared with 72% when ultrasound was used.CONCLUSION: Compared to clinical examination, ultrasound examination of the Achilles tendon substantially improves the detection of ATX and may help to better identify patients with familial hypercholesterolaemia who are at high risk for premature cardiovascular disease.